Reimagining Undergraduate Health and Social Care Education: A Workforce Fit for Purpose in a Changing Landscape of Care. A Position Paper. (April 2018) - King, Martin; Chambers, Alison; Miller, Eula; Hook, Angela; Jackson, Laura; Gurbutt, Russell; Woods-Gallagher, Shirley
NHS England's Five Year Forward View outlines new care models and the need for a workforce that has the skills, values, and competencies to deliver this vision. This is a position paper detailing the context, method, and intentions of a Health Education England funded project led by Manchester Metropolitan University in the North West of England, which the authors see as making a key contribution to addressing issues of illness, crisis, and loss in the changing landscape of health and social care provision in England. Using an action research methodology and drawing together key stakeholders from the sector, the project aims to explore the potential for creating a professional health and social care graduate workforce which meets the needs of an integrated service delivery landscape by identifying key issues to be addressed when redeveloping the undergraduate curriculum.